2015
DOI: 10.1186/s13104-015-1047-6
|View full text |Cite
|
Sign up to set email alerts
|

Local cross-border disease surveillance and control: experiences from the Mekong Basin

Abstract: BackgroundThe Mekong Basin Disease Surveillance cooperation (MBDS) is one of several sub-regional disease surveillance networks that have emerged in recent years as an approach to transnational cooperation for infectious disease prevention and control. Since 2003 MBDS has pioneered a unique model for local cross-border cooperation. This study examines stakeholders’ perspectives of these MBDS experiences, based on a survey of local managers and semi-structured interviews with MBDS leaders and the central coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The 13 articles analyzed revealed that health actions exist that provided for integration among countries, which took form in the model of international agreements. The data on the governmental policies for the integration of healthcare in international border regions permitted their organization in themes that address the scenarios of health integration agreements, particularly European countries, (11)(12)(13)(14)(15) Asian (16)(17)(18)(19) and South American countries. (20)(21)(22)(23) In these scenarios, the types and goals of the integration agreements could be identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 articles analyzed revealed that health actions exist that provided for integration among countries, which took form in the model of international agreements. The data on the governmental policies for the integration of healthcare in international border regions permitted their organization in themes that address the scenarios of health integration agreements, particularly European countries, (11)(12)(13)(14)(15) Asian (16)(17)(18)(19) and South American countries. (20)(21)(22)(23) In these scenarios, the types and goals of the integration agreements could be identified.…”
Section: Resultsmentioning
confidence: 99%
“…The research methods employed were case studies with qualitative approaches (12,(14)(15)(16)20) or simply described as qualitative. (11,13) Four studies used quantitative methods (17)(18)(19)21) and two followed the mixed method. (22,23) A synthesis of the themes addressed is displayed in chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…These include the Mekong Basin Disease Surveillance initiative, which covers 'Cambodia, Lao PDR, Myanmar, Thailand, Vietnam and the Yunnan and Guangxi provinces of China'. 83 In addition to helping to build regional capacity, in the context of emergencies, existing networks may also be utilised to provide a framework for decision-making. For example, during the Ebola outbreak in West Africa, the WHO African Vaccine Regulatory Forum provided a forum 'for regulators, ethics committees and sponsors to reach consensus on key ethical and regulatory questions'.…”
Section: Building Capacitymentioning
confidence: 99%
“…The point of entry team carried out entry and exit screening under the leadership of the Port Health Service and supported by airport, seaport and land border authorities [8]. They also worked with airline operators, national aviation authorities, immigration, maritime, custom and security officials to establish screening facilities and protocols for checking temperatures and screening of incoming and exiting passengers in Lagos and Portharcourt airports, sea ports and ground crossings.…”
Section: Safeguarding the Points Of Entry (Poe)mentioning
confidence: 99%
“…Cross-border surveillance activities including community awareness and engagement, and improved referral system and capacities would reinforce early detection and rapid control of EVD. This approach has been shown to be critical to building and sustaining effective public health response capacities at local, national and global levels [8,[18][19][20].…”
Section: Lessons Learned and Implications For Future Epidemic Preparementioning
confidence: 99%